Urgensi Pendidikan Seks Bagi Remaja - Pranitha, Derselli; Sihotang, Eleven (JURNAL DIAKONIA, 2022)
This study illustrates the urgency of sex education for adolescents. The method used in this study is a literature study. The results of this study are: sex education for teenager is very inportant but most of people misunderstood about it. Beside it, the teenegars also know sex education a little bit. Sex education aims to guide and caring for a person to understand the meaning purpose, function and of sex by providing information/ explanation of the physiological anatomy of human sexual / reproductive organs of humans that includes the genitals, as well as the dangers of venereal disease. Parents, schools, churches, and government should be responsible to educate the teenagers by given information about sex.